10.1146/annurev-med-051410-100204 (CrossRef Listing of Deleted DOIs, 2000)
Adrenal incidentalomas are increasingly encountered in routine clinical practice, driven by widespread imaging use and rising cardiometabolic disease burden. Mild autonomous cortisol secretion (MACS), characterized by low-grade, adrenocorticotropic hormone-independent cortisol excess in the absence of overt Cushingoid features, is the most common functional phenotype. Across observational cohorts, MACS is associated with a higher burden of hypertension, dysglycemia, dyslipidemia, obesity, and fractures; importantly, risk increases continuously with rising post-dexamethasone suppression test (DST) cortisol levels, including values traditionally categorized as nonfunctioning. Diagnosis centers on the 1-mg overnight DST, interpreted in clinical context and with careful attention to common interferents. The limitations of cortisol thresholds alone have prompted interest in adjunctive hormonal markers and composite clinical-biochemical risk stratification. Management is individualized, ranging from optimized cardiometabolic therapy to adrenalectomy in selected patients with clinically relevant comorbidities, while medical cortisol-modulating therapies remain investigational. This review synthesizes current evidence on the diagnosis, cardiometabolic implications, and management of MACS; highlights key uncertainties; and outlines future directions aimed at improving risk stratification and informing clinical decision-making for this increasingly prevalent condition.